The design, performance evaluation and use cases of a virtualised programmable edge node for network innovations. (8th April 2011) - Luo, Yan; Zhang, Chunhui; Ficarra, Timothy; Murray, Eric
The existing internet infrastructure faces increasing challenges on its performance, security and manageability. As a result, the need of revitalising the internet has become unprecedented. There is a strong call for flexible and open network facilities that can enable network researchers to conduct experiments and deploy new services at scale. Such facilities typically employ virtualisation technologies to support multiple experiments and sharing of network resources (CPU, bandwidth and so on). In this paper, we present the design, performance evaluation and use cases of a programmable edge node (PEN) prototype, as a part of the GENI Spiral One projects. This PEN is equipped with both general-purpose multicore processors at the host and application-specific multicore processors at the network interfaces, providing effective isolation of experiments and measurements. We conduct experiments to evaluate the performance of the prototype and describe the use case of such a virtualisable programmable network node within an operational testbed.